Pictorial Cross-Currents between Hawthorne and Atwood: Negotiating with the Dead - Patricia Simonson (Perífrasis. Revista de Literatura, Teoría y Crítica)
This paper analyzes the way in which a contemporary Canadian novelist, Margaret Atwood, uses the work of a canonical nineteenth-century American novelist, Nathaniel Hawthorne, to define her own position as a writer, while at the same time criticizing and transforming her precursor’s reflection on the writer’s task. I identify this process in Atwood’s 1996 novel, Alias Grace: it takes the form of a rewriting of Hawthorne’s most famous novel, The Scarlet Letter. An important connection between the two writers is their common use of visual art to pose, and potentially to resolve, the problems they encounter as artists in a hostile environment.